Analysis of Law No. 39 of 2007 Concerning Amendments to The Law on Excise to Protect Lives (Hifdzunnafs) on The Discourse on The Imposition of Customs Duties on Sweetened Packaged Beverage Products - Susanto, Heru (Et-Tijarie, 2023)
The purpose of this study is to analyze the discourse on the imposition of customs duties on sweetened packaged beverage products in the perspective of hifdz annafs.The research method uses qualitative research with a literature review approach. The literature review was analyzed descriptively.The results of the study show that increasing the customs tax on sugary drinks from Al-Nafs (protecting the soul), is a benefit because consuming sweetened packaged drinks can cause harm in the soul in the long term. Thus, the imposition of customs duties on sweetened packaged drinks is included in the category of ḥifẓ an-nafs (nourishing the soul).